El centro como ausencia: la memoria en el capítulo II de Los detectives salvajes de Roberto Bolaño - Espinosa H., Patricia (2017)
The present article will address chapter II “The savage detectives (1976- 1996)”, which introduces fifty-four characters that give testimony regarding poets Arturo Belano and Ulises Lima. The absence of these poets is what allows for them to be present in each one of the testifying subjects’ memory. The narration, then, constructs a place of memory for Belano and Lima to inhabit, generating in this way a violent interruption that constitutes a rejection of the traditional novel format since it relocates its fundamental elements, namely, the protagonist and the narrator. This chapter can, therefore, be interpreted as a center that denies the concept of center by presenting itself as the very occurrence of that which remainson the run.